A Majority of Single Versus Double-Row Rotator Cuff Repair Comparisons Fail to Consider Modern Single-Row Techniques: A Systematic Review. Issue 5 (May 2020) - Maassen, Nicholas H.; Somerson, Jeremy S.
Abstract : Background: There is considerable published research comparing single-row (SR) and double-row (DR) rotator cuff repairs. Conclusions of primary studies as well as multiple meta-analyses have differed. One underexplored factor has been the variability in techniques that are identified as "single-row" or "double-row." Our goal was to conduct a systematic review of primary research and meta-analyses comparing SR and DR fixation techniques, with attention to the specific technique types compared. Methods: We evaluated meta-analyses and individual studies that directly compared SR and DR repairs. Primary studies from 8 high-quality meta-analyses published prior to 2014, and any Level-III or higher studies published from 2014 to 2019, were included. Specific techniques of repair were identified, and the manuscripts were classified on the basis of the specific type of simple or complex SR or DR repair that was performed. Conclusions of the studies were then assessed according to these classifications. Results: Twenty-two studies met the eligibility criteria; 9 were Level-I studies, 7 were Level-II, and 6 were Level-III. Of the 22 studies, only 3 (14%) of the studies compared a biomechanically superior complex SR technique and a DR repair. The remaining 19 (86%) of the studies utilized biomechanically inferior, simple SR techniques in their comparisons. Conclusions: While there is a large amount of published evidence comparing SR and DR rotator cuff repair techniques, there are few studies assessing how the strongest SR techniques compare with DR techniques. This identifies a deficiency in the current understanding of rotator cuff repair techniques. Future studies specifically designed with these techniques in mind will help to further the understanding of which technique is clinically and financially superior in this continuously changing medical environment. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.